1987
DOI: 10.1080/15287398709530998
|View full text |Cite
|
Sign up to set email alerts
|

Method of measuring deposition of unlabeled monodisperse microspheres in rat lungs

Abstract: A system to simultaneously measure the total deposition of four different sizes of monodisperse microspheres in normal and damaged lungs of rats was developed and tested. The system reproducibly measured the deposition of microspheres in control rats, and the procedure was shown to be sufficiently sensitive to measure ozone-induced changes in deposition rates. Rats exposed to 1.2 ppm ozone 6 h/d for 2 consecutive days showed greater deposition of the 1.09-micron-, 2.02-micron-, and 2.99-micron- but not of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A number of published studies cannot be used because they reported deposition in the lungs normalized to the deposition in or on the animal and not to what was inhaled (Newton & Pfledderer, 1986;Dahlback et al, 1989), used anesthetized animals (McMahon et al, 1977;Johnson & Ziemer, 1971;Raabe et al, 1977), or used cannulated animals (Shiotsuka et al, 1987).…”
Section: Discussionmentioning
confidence: 97%
“…A number of published studies cannot be used because they reported deposition in the lungs normalized to the deposition in or on the animal and not to what was inhaled (Newton & Pfledderer, 1986;Dahlback et al, 1989), used anesthetized animals (McMahon et al, 1977;Johnson & Ziemer, 1971;Raabe et al, 1977), or used cannulated animals (Shiotsuka et al, 1987).…”
Section: Discussionmentioning
confidence: 97%